2000
DOI: 10.1046/j.1471-4159.2000.0751447.x
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Enhances Uptake of Amyloid β‐Protein by Microglia Derived from the Human Cortex

Abstract: Abstract:In recent years, inflammatory mechanisms have been increasingly appreciated as important steps in the pathology of Alzheimer's disease (AD). There are two pathological defects in AD: chronic inflammation and impaired clearance of amyloid ␤-peptide (A␤). In the periphery, estrogen both increases macrophage phagocytosis and has antiinflammatory effects. If estrogen had a similar effect in the CNS, it could reverse inflammatory defects in AD. Although microglia are a key component of the immune system an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
89
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 147 publications
(94 citation statements)
references
References 50 publications
5
89
0
Order By: Relevance
“…Another mechanism by which estrogen replacement therapy could impact risk of Alzheimer's disease has been reported by Rogers and colleagues (Li et al 2000). These investigators found that 17␤-estradiol significantly increased the uptake of ␤-amyloid by microglia.…”
Section: Estrogen Regulation Of ␤-Amyloid Deposition and Microglial Fmentioning
confidence: 85%
See 1 more Smart Citation
“…Another mechanism by which estrogen replacement therapy could impact risk of Alzheimer's disease has been reported by Rogers and colleagues (Li et al 2000). These investigators found that 17␤-estradiol significantly increased the uptake of ␤-amyloid by microglia.…”
Section: Estrogen Regulation Of ␤-Amyloid Deposition and Microglial Fmentioning
confidence: 85%
“…These investigators found that 17␤-estradiol significantly increased the uptake of ␤-amyloid by microglia. The expression of ER␤ was also up-regulated by estrogen treatment (Li et al 2000).…”
Section: Estrogen Regulation Of ␤-Amyloid Deposition and Microglial Fmentioning
confidence: 93%
“…Estradiol increases APP expression in neuronal cells ( [35,109,256]) and reduces Ab peptide production while enhancing its clearance ( [36,137,256]). A modification of Ab levels was induced by estradiol treatment in the Tg2576 AD model [267].…”
Section: Estrogens and Alzheimer's Diseasementioning
confidence: 99%
“…Estrogen deficiency accelerated the formation of Amyloid plaque in mice (Yue et al, 2005). Estrogen treatment reduced the level of Amyloid (Jaffe et al, 1994;Xu et al, 1998) and its availability through enhancing the uptake of Amyloid by microglia (R. Li et al, 2000). In vitro estrogen treatment inhibited the formation of toxic Amyloid oligomers (Morinaga et al, 2007).…”
Section: Amyloid βmentioning
confidence: 99%